Design of a process control laboratory curriculum incorporating simulation modules and hands-on training for enhanced learning experience - Lock, Serene Sow Mun; Lock, Irene Sow Mei; Lam, Ghai Lim (Academica Press Solutions, 2025)
Integrating Industry 4.0 principles into laboratory programs is essential for mastering modern process control. However, many existing curricula rely heavily on direct instrument use, which may not fully prepare students for Industry 4.0 requirements. In response, Universiti Teknologi PETRONAS has introduced an updated, simulation-focused curriculum, starting with the CEB3032 Chemical Engineering Laboratory III course for the January and May 2021 cohorts, which included 207 and 162 students, respectively. These cohorts faced limited hands-on training opportunities due to COVID-19, underscoring the need for enhanced practical skill development through simulation. To prepare, the university carefully selected suitable experiments for process simulation, modeling them using dynamic simulation tools. Students were exposed to methodologies such as Euler's, RungeKutta, and Gear methods for lumped parameter systems, and finite difference methods for distributed systems, to understand the calculation basis underlying the dynamic system. Within this curriculum, students participated in simulation creation, experimentation, results documentation, and comparison with conventional laboratory results. Advanced Bloom's Taxonomy and the Five Es Inquiry-Based Learning model were key components, allowing students to design their own labs and explore foundational control principles. Feedback and performance metrics highlighted the program's success, with improved student performance indicators, including higher rates of top grades (e.g., A's) and a rise in median scores. Approximately 30% more students earned grades from B to A, and many reported that process simulation had significantly strengthened their ability to apply theoretical knowledge in laboratory settings. This approach's success points to its potential for broader academic adoption, offering a scalable, cost-effective model adaptable to various engineering curricula using existing simulation resources.